An Overview of Sino-nasal masses: A study from Dhaka Medical College Hospital - Talukder, Debesh Chandra; Sarker, Satinath Chandra; Ahasan, Syed Ali; Haque, Muhammad Mozammal; Arefin, Mostafa Kamal; Musabbir, Nadira; Rahman, Chowdhury Md Mushfiqur; Kabir, SM Humayun (Journal of Dhaka Medical College, 2020)
Background: To study the incidence, clinical presentation and to observe comparison of different sinonasal masses. Materials and Methods: This Prospective study was carried out from January 2017 to December 2018. Data were collected from 100 patients presented with sinonasal masses. This study is based on history, clinical, radiological, laboratory and histopathological examination. Results: During the study period, 100 patients presented with sinonasal masses (male 60, female 40; age group 8-70 years).Nasal polyploid masses were non-neoplastic in 70 (70%) subjects, and neoplastic in 30 (30%) cases. Nasal obstruction was the most common (95%) presenting complaint, followed by rhinorrhoea (48%), hyposmia (30%), intermittent epistaxis (17%), headache (15%), facial swelling (10%) and eye-related symptoms (10%). The most common site of origin of polyploid masses was the middle meatus (54%) followed by the lateral wall of the nasal cavity (15%) and superior meatus (11%). unilateral nasal masses was present in 49% patients, while the remaining patients had bilateral nasal masses. Allergic (60%) and inflammatory (28.5%) polyps were the most common non-neoplastic mass, inverted papilloma (41.17%) and haemangioma (35.29%) were most common benign neoplastic mass; 92.3% of all malignant masses were squamous cell carcinoma. Surgery was the major mode of treatment. it included Caldwell-luc operation (7%), polypectomy (10%), excision of mass (25.0%) and functional endoscopic sinus surgery (44%). Malignancies were treated with radiotherapy or Surgery followed by radiotherapy or Chemoradiotherapy. Conclusions: The masses in nasal cavity, paranasal sinuses, and nasopharynx encompass a wide spectrum of common and rare diseases and are very common lesions encountered in clinical practice. Endoscopic examination and advanced imaging technique help to reach a presumptive diagnosis but histopathological examination remains the mainstay of final definitive diagnosis. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 49-53